Capacity Building, Management and Sustainability Values - Maher, Nevenka (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
Reality context, European Union policy priorities, building people wellbeing and system resilience, research and innovation promotion, - they all demand quality management and its sustainability within actual changes. The sustainability concept puts EU citizen′s health in focus: the health is a value and it is the driver of productivity. The healthcare system is the central part within the country′s resilience: Only healthy people enable productivity and added value. The added value is the key driver of competition also within the Draghi′s Report, prepared for European Commission and has been used for existing strategy correction and for future financial perspective 2028-2034 preparation. The paper exposes importance of education and training of three different dimension of capacities (individual, institutional and system) within the real context of health policy. Management is to be skilled in conceptual managing action and to be involved in methodology preparation and removing its barriers.